Spark plug

CN117461227BActive Publication Date: 2026-10-30NITERRA CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280041637.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-06-14
Filing Date
2022-06-14
Publication Date
2026-10-30
Estimated Expiration
2042-06-14

AI Technical Summary

Technical Problem

然而,若伴随于绝缘体的小径化而绝缘体的壁部的厚度变小,则变得无法忽视气孔的存在,有时气孔会对绝缘体的耐电压性能的下降造成影响

Benefits of technology

[0018]根据本发明,能够提供具备耐电压性能优异的绝缘体的火花塞。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117461227B_ABST
    Figure CN117461227B_ABST
Patent Text Reader

Abstract

The spark plug of the present application is provided with an insulator composed of an alumina-based sintered body, the insulator having a long leg portion disposed on the tip end side, a stem portion disposed on the rear end side of the long leg portion, which is larger in diameter than the long leg portion, and a flange portion disposed on the rear end side of the stem portion, which is larger in diameter than the stem portion. In a state where a cut surface obtained by cutting the stem portion at an arbitrary position in the axial direction in a direction perpendicular to the axial direction is mirror-polished, 20 observation regions of 185 μm x 250 μm are set in a manner not overlapping each other, and the square of the length of the periphery of each of a plurality of pores contained therein is calculated. In this case, the average of the squares of the 20 pores having the larger square is 2200 μm 2 Hereinafter, the proportion of the total area of all the pores contained in the 20 observation regions with respect to the total area of the 20 observation regions (100%) is 5% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to spark plugs. Background Technology

[0002] Spark plugs used in internal combustion engines include those with a cylindrical insulator composed primarily of an alumina-based sintered body (e.g., Patent Document 1). In recent years, the insulator diameter in such spark plugs has been reduced due to requirements for smaller diameters. However, this reduction in diameter thins the wall thickness of the cylindrical insulator, sometimes causing problems with its voltage withstand performance. Therefore, there has been a pursuit in recent years to further improve the voltage withstand performance of the insulator.

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: Japanese Patent Application Publication No. 2020-57559

[0006] (The problem that the invention aims to solve)

[0007] Within the walls of cylindrical insulators, there are typically some degree of fine pores (voids). These pores are unavoidable during the insulator's manufacturing process, and their presence is generally considered a problem, except in cases of extremely large pores (e.g., pores exceeding 5,000 μm in diameter). However, if the insulator's diameter decreases along with the thickness of its walls, the presence of pores becomes significant, and sometimes they can negatively impact the insulator's withstand voltage performance. Summary of the Invention

[0008] The purpose of this invention is to provide a spark plug with an insulator having excellent voltage resistance.

[0009] (Methods used to solve problems)

[0010] The inventors have discovered that in a spark plug having an insulator made of an alumina-based sintered body, if there are pores (voids) of a certain size and with an uneven surface inside the main body of the insulator, a localized electric field concentration occurs in the uneven contour portion surrounding the pores during the use of the spark plug, causing damage to the insulator.

[0011] Furthermore, through intensive research conducted by the inventors, it was discovered that in a spark plug having an insulator composed of an alumina-based sintered body, if the outline shape, size, and proportion of pores in the main body of the insulator are controlled in a manner that satisfies the conditions specified later, the voltage withstand performance of the insulator can be ensured, thus completing the invention of this application.

[0012] The means for solving the aforementioned problem are as follows. That is,

[0013] <1> A spark plug includes an insulator comprising: a long leg, which is cylindrical and extends along an axial direction and is disposed at the front end; a main body, which is disposed at the rear end of the long leg and has a larger diameter than the long leg; and a flange, which is disposed at the rear end of the main body and has a larger diameter than the main body. The insulator is made of an alumina-based sintered body. In a mirror-polished surface obtained by mirror polishing the cut surface, 20 observation areas of 185μm × 250μm are defined in a non-overlapping manner, and the square value P of the outer perimeter length P [μm] of each of the 20 observation areas is calculated for each of the multiple pores contained in the 20 observation areas. 2 [μm 2 In the case of […], the square value P 2 [μm 2 The square value P of the largest 20 upper pores 2 [μm 2 The average value is 2200 μm. 2 The cut surface is obtained by cutting the main stem at any position in the axial direction in a direction perpendicular to the axial direction, and the ratio T[%] of the total area of ​​all pores contained in the 20 observation areas to the total area (100%) of the 20 observation areas is 5% or less.

[0014] <2> According to the above <1> The spark plug, in which the cumulative 50% of the cumulative distribution of the area of ​​the pores in the 20 observation areas respectively exceeds 3 μm 2 The value of .

[0015] <3> According to the above <1> or <2> The spark plug, wherein the proportion T is 3% or less.

[0016] <4> According to the above <1> ~ <3> For any of the aforementioned spark plugs, the thickness of the main body is less than 2.0 mm.

[0017] (Invention Effects)

[0018] According to the present invention, it is possible to provide a spark plug having an insulator with excellent voltage resistance. Attached Figure Description

[0019] Figure 1 This is a cross-sectional view along the axial direction of the spark plug according to Embodiment 1.

[0020] Figure 2 It is an illustrative diagram that schematically shows the cross-section of the main stem.

[0021] Figure 3 This is an explanatory diagram showing the binarized image obtained by binarizing the SEM image corresponding to the observation area.

[0022] Figure 4 This is a schematic diagram illustrating the arbitrary selection of one pore from all the pores.

[0023] Figure 5 This is a schematic diagram illustrating a method for determining the through-voltage of a test sample using a withstand voltage test in water. Detailed Implementation

[0024] <Implementation Method 1>

[0025] Referring to the spark plug 1 according to Embodiment 1 of the present invention... Figures 1-5 While explaining. Figure 1 This is a cross-sectional view of the spark plug 1 according to Embodiment 1 along the AX direction. Figure 1 The single-dot dashed line extending vertically shown is the axis AX of spark plug 1. Figure 1 In the diagram, the length direction of spark plug 1 (axis AX direction) corresponds to... Figure 1 The up and down direction. In Figure 1 The lower side shows the front end of spark plug 1. Figure 1 The upper side shows the rear end side of spark plug 1.

[0026] Spark plug 1 is installed in the engine of a car (an example of an internal combustion engine) and is used to ignite the air-fuel mixture in the engine's combustion chamber. Spark plug 1 mainly includes an insulator 2, a center electrode 3, a ground electrode 4, terminal fittings 5, a main body fitting 6, a resistor 7, and sealing components 8 and 9.

[0027] Insulator 2 is a generally cylindrical component extending in the axial direction AX that contains a through hole 21 inside. Details of insulator 2 will be described later.

[0028] The main component 6 is a member used when installing the spark plug 1 onto the engine (specifically, the engine cover). It is a cylindrical component extending along the AX axis as a whole, and is made of a conductive metal material (e.g., low-carbon steel). A threaded portion 61 is formed on the outer peripheral surface of the front end side of the main component 6. Furthermore, an annular washer G is embedded at the rear end of the threaded portion 61 (the so-called threaded end). The washer G is annular and formed by bending a metal plate. This washer G is positioned between the rear end of the threaded portion 61 and a seat portion 62 positioned further back than the threaded portion 61, sealing the gap formed between the spark plug 1 and the engine (engine cover) when the spark plug 1 is installed in the engine.

[0029] A tool engaging portion 63 is provided at the rear end of the main body component 6 for engaging tools such as wrenches when installing the main body component 6 onto the engine. Furthermore, a thin-walled tightening portion 64 that bends radially inward is provided at the rear end of the main body component 6.

[0030] Furthermore, the main body component 6 has a through hole 65 extending along the axial direction AX, through which the insulator 2 is held within the main body component 6. The rear end of the insulator 2 extends outward from the rear end of the main body component 6. Figure 1 The upper side of the insulator 2 protrudes significantly. In contrast, the front end of the insulator 2 extends outward from the front end of the main body component 6. Figure 1 (The lower side) is slightly protruding.

[0031] An annular region is formed between the inner circumferential surface of the portion from the tool engaging part 63 to the tightening part 64 in the main body component 6 and the outer circumferential surface of the insulator 2 (the outer circumferential surface of the rear cylindrical part 25 described later). A first ring member R1 and a second ring member R2, arranged in annular form and separated from each other in the axial direction AX, are disposed in this region. Powdered talc 10 is filled between the first ring member R1 and the second ring member R2. The rear end of the tightening part 64 is bent radially inward and fixed to the outer circumferential surface of the insulator 2 (the outer circumferential surface of the rear cylindrical part 25 described later).

[0032] Furthermore, the main body component 6 includes a thin-walled compression deformation portion 66 disposed between the seat portion 62 and the tool engagement portion 63. During the manufacturing of the spark plug 1, the compression deformation portion 66 is compressed and deformed by pressing it towards the front end by the tightening portion 64 fixed to the outer peripheral surface of the insulator 2. Through this compression deformation by the compression deformation portion 66, the insulator 2 is pressed towards the front end within the main body component 6 via the first ring member R1, the second ring member R2, and the talc 10. At this time, the outer peripheral surface of a portion of the insulator 2 that extends outward in a ring shape (the first diameter expansion portion 26 described later) is pressed against the surface of the step portion 66 provided on the inner peripheral side of the main body component 6, with the gasket P1 placed in the middle. Therefore, even if gas from the combustion chamber of the engine enters the gap formed between the main body component 6 and the insulator 2, the gasket P1 disposed in the gap prevents the gas from leaking outward.

[0033] With the insulator 2 assembled inside the main body component 6, a center electrode 3 is disposed inside the insulator 2. The center electrode 3 has a rod-shaped center electrode body 31 extending along the AX direction and a generally cylindrical (generally circular plate-shaped) end (center electrode tip) 32 mounted at the front end of the center electrode body 31. The center electrode body 31 is a member whose length in the longitudinal direction is shorter than that of the insulator 2 and the main body component 6, and is held in the through hole 21 of the insulator 2 such that its front end is exposed laterally to the outside. The rear end of the center electrode body 31 is received inside the insulator 2 (through hole 21). The center electrode body 31 has an electrode base material 31A disposed on the outside and a core portion 31B embedded inside the electrode base material 31A. The electrode base material 31A is formed, for example, using nickel or an alloy with nickel as the main component (e.g., NCF600, NCF601). The core 31B is formed of copper, which has a higher thermal conductivity than the electrode substrate 31A, or a nickel-based alloy with copper as the main component.

[0034] Furthermore, the central electrode body 31 includes an electrode flange portion 31a mounted at a predetermined position along the AX axis, an electrode head 31b (a portion further rearward than the electrode flange portion 31a), and an electrode leg portion 31c (a portion further frontward than the electrode flange portion 31a). The electrode flange portion 31a, when housed within the insulator 2, is supported by a stepped portion 23a (described later) formed on the inner circumferential surface of the insulator 2. The front end of the electrode leg portion 31c (that is, the front end of the central electrode body 31) protrudes further forward than the front end of the insulator 2.

[0035] The end 32 is generally cylindrical (generally circular plate-shaped) and is joined to the front end of the central electrode body 31 (the front end of the electrode leg 31c) by resistance welding, laser welding, or the like. The end 32 is made of a material with a high melting point noble metal as the main component (e.g., an iridium-based alloy with iridium (Ir) as the main component).

[0036] Terminal fitting 5 is a rod-shaped member extending in the AX direction, installed by insertion into the rear end of the through hole 21 of the insulator 2. Terminal fitting 5 is disposed within the insulator 2 (through hole 21) at a position further rear-end than the center electrode 3. Terminal fitting 5 is made of a conductive metallic material (e.g., low-carbon steel). It should be noted that the surface of terminal fitting 5 may also be plated with nickel or the like for corrosion protection purposes.

[0037] The terminal accessory 5 includes a rod-shaped terminal leg 51 disposed on the front end side, a terminal flange 52 disposed on the rear end side of the terminal leg 51, and a cap assembly portion 53 disposed further rearward than the terminal flange 52. The terminal leg 51 is inserted into the through hole 21 of the insulator 2. The terminal flange 52 is the portion that protrudes from the rear end of the insulator 2 and is locked toward the rear end. The cap assembly portion 53 is the portion for assembling a spark plug cap (not shown) connected to a high-voltage cable, through which a high voltage for generating a spark discharge is applied from the outside.

[0038] The resistor 7 is disposed within the through hole 21 of the insulator 2 between the front end of the terminal fitting 5 (the front end of the terminal leg 51) and the rear end of the center electrode 3 (the rear end of the center electrode body 31). The resistor 7 has a resistance value of 1kΩ or more (e.g., 5kΩ) and functions to reduce electromagnetic noise during spark generation. The resistor 7 is composed of a composition including glass particles as the main component, ceramic particles other than glass, and a conductive material.

[0039] A gap is provided between the front end of the resistor 7 and the rear end of the center electrode 3 within the through hole 21, and a conductive sealing member 8 is provided to fill this gap. Similarly, a gap is also provided between the rear end of the resistor 7 and the front end of the terminal fitting 5 within the through hole 21, and a conductive sealing member 9 is provided to fill this gap. Each sealing member 8 and 9 is, for example, composed of a conductive material containing glass particles (such as B2O3-SiO2) and metal particles (such as Cu and Fe).

[0040] The grounding electrode 4 comprises a grounding electrode body 41 joined to the front end of the main body accessory 6 and a prism-shaped grounding electrode tip 42. The grounding electrode body 41 is generally constructed of a plate bent into a roughly L-shape midway, and its rear end 41a is joined to the front end of the main body accessory 6 by resistance welding or the like. Thus, the main body accessory 6 and the grounding electrode body 41 are electrically connected. The grounding electrode body 41, for example, is formed using nickel or a nickel-based alloy (e.g., NCF600, NCF601) with nickel as its main component, similar to the main body accessory 6. The grounding electrode tip 42, like the end 32 of the center electrode 3, is constructed of an iridium-based alloy with iridium (Ir) as its main component. The grounding electrode tip 42 is joined to the front end of the grounding electrode body 41 by laser welding.

[0041] The ground electrode tip 42 at the front end of the ground electrode body 41 and the end 32 at the front end of the center electrode 3 are arranged in a spaced-apart and opposite manner. That is, there is a gap SP between the end 32 at the front end of the center electrode 3 and the ground electrode tip 42 at the front end of the ground electrode 4. If a high voltage is applied between the center electrode 3 and the ground electrode 4, a spark discharge is generated in the gap SP in a manner approximately along the axial direction AX.

[0042] Next, insulator 2 will be described in detail. Insulator 2 is generally a cylindrical shape extending slenderly along the AX axis, as shown below. Figure 1 As shown, the insulator 2 contains a through hole 21 extending in the AX direction. The insulator 2 is composed of a cylindrical alumina-based sintered body with alumina as the main component. The insulator 2 includes: a long leg portion 22 disposed at the front end; a main body portion 23 disposed at the rear end of the long leg portion 22, with a larger diameter than the long leg portion 22; and a flange portion 24 disposed at the rear end of the main body portion 23, with a larger diameter than the main body portion 23. It should be noted that a first diameter-enlarging portion 26 is provided between the long leg portion 22 and the main body portion 23, and a second diameter-enlarging portion 27 is provided between the main body portion 23 and the flange portion 24.

[0043] The long leg portion 22 is generally a slender cylindrical shape (cylindrical shape) with its outer diameter gradually increasing from the front to the rear, and has an outer diameter smaller than that of the main body 23 and the first expansion portion 26. The long leg portion 22 is exposed to the combustion chamber when the spark plug 1 is installed in the engine (engine cover).

[0044] The flange portion 24 is located approximately at the center of the insulator 2 along the AX axis and is in the shape of a ring. A resistor 7 is disposed in the through hole 21 located inside the flange portion 24.

[0045] The first enlarged diameter portion 26 is the part connecting the long leg portion 22 and the main body 23, and is cylindrical (annular) in shape with the outer diameter gradually increasing from the front to the rear. When the insulator 2 is assembled to the main body accessory 6, the outer surface of the first enlarged diameter portion 26 in the insulator 2 is positioned relative to the surface of the stepped portion 66 provided on the inner circumference side of the main body accessory 6 so that the gasket P1 is placed in the middle.

[0046] The second diameter expansion section 27 is the part that connects the main body 23 and the flange section 24. It is cylindrical (ring-shaped) with an outer diameter that is larger than that of the first diameter expansion section 26 and gradually increases in size from the front to the rear.

[0047] The main stem 23 is cylindrical (circular) with an outer diameter set to be approximately the same along the AX axis. Figure 1The diagram shows the area L1 occupied by the main stem 23 in the AX direction. With the insulator 2 assembled to the main body fitting 6, a slight gap (space) exists between the outer surface (outer peripheral surface) of the main stem 23 and the inner surface (inner peripheral surface) of the main body fitting 6. An annular step portion 23a is provided on the inner side (inner peripheral surface side) near the front end of the main stem 23. With the central electrode body 31 of the central electrode 3 housed in the through hole 21 of the insulator 2, the electrode flange portion 31a of the central electrode body 31 is supported by the surface of the step portion 23a. The thickness (radial thickness) of the wall portion of the main stem 23 is greater than the thickness of the wall portion of the long leg portion 22. Furthermore, the thickness of the wall portion of the main stem 23 from the front end side to the portion where the step portion 23a is formed is greater than the thickness of the wall portion further rearward.

[0048] The outer periphery of the main body 23 is exposed to the atmosphere (air), meaning that the main body 23 is in an environment where it is more difficult for current to pass through compared to the long leg 22. Therefore, the wall thickness of the main body 23 is set to be greater than that of the long leg 22.

[0049] In this specification, unless otherwise specified, "thickness of the main body 23" refers to the thickness of the wall portion of the main body 23 where the wall thickness is approximately constant (that is, the portion further back than the step portion 23a). The thickness of the main body 23 is not particularly limited as long as it does not impair the purpose of the invention, but it can be, for example, 3.0 mm or less, or 2.0 mm or less. If the thickness of the main body 23 is 2.0 mm or less, the technical effects of the invention are more significantly realized.

[0050] It should be noted that the insulator 2 also includes a cylindrical rear section 25 that is connected to the rear end of the flange 24 and extends in the AX direction. The rear section 25 has an outer diameter smaller than that of the flange 24. A rod-shaped terminal leg 51, etc., of the terminal fitting 5 is provided in the through hole 21 inside the rear section 25.

[0051] The main body 23 is the part of the insulator 2 most susceptible to the effects of diameter reduction, and insulation failure is easily caused by diameter reduction. Therefore, if the main body 23 has an internal structure containing all the pores that satisfy at least conditions 1 and 2 shown below, an insulator 2 (spark plug 1) with excellent voltage resistance can be obtained.

[0052] <Condition 1>

[0053] In a mirror-polished surface obtained by mirror polishing a cut surface (i.e., a cut surface in which the main stem 23 is cut at any position in the AX direction perpendicular to the AX direction) 23b, 20 observation areas of 185μm × 250μm (rectangular observation areas of 185μm in length and 250μm in width) are set in a non-overlapping manner, and the square value of the outer perimeter length P[μm] of the pores contained in these 20 observation areas is calculated for each pore. 2 [μm 2 In the case of [ ], to make the square value P 2 [μm 2 The square value P of the largest 20 upper pores 2 [μm 2 The average value of ] is 2200μm 2 In the following manner, pores are contained in the main body 23 of the insulator 2.

[0054] <Condition 2>

[0055] In all the pores, the ratio T[%] of the total area of ​​all the pores contained in the 20 observation areas to the total area (100%) of the 20 observation areas is less than 5%.

[0056] Here, while referring to Figures 2-4 And so on, to provide a more detailed explanation of conditions 1 and 2 above. Figure 2 This is an explanatory diagram schematically showing the cross-section 23b of the main stem 23. Figure 2 The diagram shows a cut surface 23b obtained by cutting the main stem 23 at any position along the AX axis in a direction perpendicular to the AX axis, and then grinding it into a mirror-like surface after cutting. In this specification, the mirror-polished surface of the cut surface 23b is sometimes referred to as "mirror-polished surface 23b" using the same reference numerals as the cut surface 23b.

[0057] The mirror polishing treatment of the cut surface 23b is performed using known methods such as diamond grinding stones and diamond paste. The mirror polishing treatment continues until the surface roughness (Ra) of the cut surface 23b becomes, for example, about 0.001 μm.

[0058] The mirror-polished surface 23b of the main body 23 was observed using a scanning electron microscope (SEM). Therefore, carbon vapor deposition for imparting conductivity can also be performed on the mirror-polished surface 23b as needed. It should be noted that the accelerating voltage of the SEM was set to, for example, 20 kV, and the SEM magnification was set to, for example, 500x.

[0059] like Figure 2 As shown, the mirror-polished surface 23b is annular in shape. Twenty observation areas X, each 185μm × 250μm in size, are arranged in a ring-like column on this annular surface 23b without overlapping. Each observation area X is obtained as a SEM image of a predetermined portion of the mirror-polished surface 23b captured using SEM. Figure 2 In the diagram, multiple observation regions X are schematically represented. It should be noted that... Figure 2 In order to distinguish the observation areas X from each other, each figure's reference numeral X is given a suffix (a number from 1 to 20). For example, observation area X1 is the first set observation area X, and observation area X20 is the twentieth set observation area X.

[0060] For the 20 SEM images corresponding to the 20 observation regions X set in this way, image analysis processing (two-dimensional image analysis processing) is performed using well-known image analysis software (e.g., WinROOF (registered trademark)) executed on a computer.

[0061] In the image analysis and processing, firstly, for each SEM image, a size correction (calibration) is performed based on the scale bar attached to the SEM image. Next, the corrected SEM image is binarized. Figure 3 This is an explanatory diagram showing the binarized image obtained by binarizing the SEM image corresponding to the observation region X. In the binarization process, the luminance (brightness) of each pixel in the SEM image is binary-coded using a specified threshold (e.g., threshold = 118). That is, for pixels with luminance below the threshold, the luminance of that pixel is "0", and for pixels with luminance exceeding the threshold, the luminance of that pixel is "255". By eliminating intermediate gray levels through this binary-coding, a binarized image is obtained. Figure 3 In the binary image, the pores 11 are represented in black, and the rest (ceramic part) 12 is represented in white.

[0062] Then, all the pores (voids) contained in the binarized image corresponding to the observation area X are extracted, and the length P [μm] of the outer perimeter of each extracted pore is measured. Figure 4 This is an explanatory diagram schematically showing one pore 11 randomly selected from all the pores. Furthermore, for each extracted pore, the square of the measured pore perimeter length P [μm] is calculated. 2 [μm 2 Square value P 2 [μm 2 ] Calculate all the pores 11 contained in the 20 observation areas X.

[0063] In this way, the square value P is calculated for all pores 11. 2 [μm 2 Then, from these pores 11, with a square value P 2 [μm 2 Select the top 20 stomata in descending order of size. Then, calculate the squared value P of these top 20 stomata. 2 [μm 2 The average value of the squared value P. In this embodiment, the squared value P... 2 [μm 2 The average value was set to 2200 μm. 2 the following.

[0064] The square value P 2 [μm 2 The average value is 2200 μm. 2 The following conditions mean that the outline shape of the pores contained in the main body 23 is preferably closer to a true circle in the cut surface (mirror-polished surface) 23b, and the size of the pores contained in the main body 23 is preferably smaller.

[0065] Here, regarding the square value P of the stomata... 2 [μm 2 The technical significance of this further needs to be explained. It should be noted that, here, we will use an arbitrary pore extracted from a binarized image as an example. The outline shape of the pore can be evaluated using its concavity / convexity as an indicator. The concavity / convexity of the pore is determined by (P... 2 / A)×(1 / 4π) represents the area of ​​the pore. As mentioned above, P represents the length of the pore's outer perimeter P [μm], and A represents the area of ​​the pore [μm]. 2 Furthermore, the size of the stomata can be determined using the area A [μm]. 2 Use this to evaluate.

[0066] Therefore, it is empirically known that for a single pore, V, as an index that evaluates both "profile shape" and "size" in a concentrated manner, can be obtained by utilizing the pore's roughness (P). 2 / A)×(1 / 4π)) and the area A[μm of the pores 2 The product of (P) 2 / A)×(1 / 4π)×A). In this case, the index V is obviously related to the square value P. 2 [μm 2 Therefore, in this embodiment, the square value P of the pore's outer perimeter length P [μm] is used as an indicator to evaluate both the "outline shape" and "size" of a single pore. 2 [μm 2 ].

[0067] It should be noted that the area A [μm] of each pore extracted from the binarized image corresponding to the observation area X is also measured. 2 The measured area A [μm] of each pore. 2 It shall be used in accordance with the provisions of condition 2 described later.

[0068] Furthermore, as shown in condition 2 above, the pores 11 in the internal structure of the main body 23 of the insulator 2 were adjusted so that the ratio T [%] of the total area of ​​all pores contained in all observation areas X to the area of ​​all observation areas X (the total area of ​​20 observation areas X) (100%) was less than 5%. The total area of ​​all pores in condition 2 refers to the area A [μm] of the pores measured with respect to all pores. 2 The sum of ] . It should be noted that, in this embodiment, the area A [μm] of one pore. 2 The preferred size was adjusted to 5,000 μm. 2 Below. For reference, in order to compare with the size of pore 11, in Figure 3 In the binarized image, an area of ​​approximately 5,000 μm is shown. 2 A circle.

[0069] Furthermore, in addition to conditions 1 and 2 mentioned above, the internal structure of the main stem 23 can also be adjusted in a manner that satisfies the conditions shown below. Specifically, when the area distribution of stomata is approximated by a log-normal distribution for each of the 20 observation regions X, and the cumulative 50% area of ​​the cumulative distribution of the stomata area is obtained, this cumulative 50% area can be greater than 3 μm. 2 The value of . If the main body 23 satisfies such conditions, then an insulator 2 with excellent impact resistance can be obtained.

[0070] Furthermore, the internal organization of the principal cadre 23 can also be adjusted in a manner that satisfies the conditions shown below. Specifically, the proportion T [%] shown in condition 2 above can also be 3% or less.

[0071] Next, the manufacturing method of insulator 2 will be explained. Insulator 2 is manufactured in a manner that satisfies conditions 1 and 2 as described above. As for the manufacturing method of insulator 2, there are no particular restrictions as long as the final obtained insulator 2 satisfies conditions 1 and 2. Here, an example of the manufacturing method of insulator 2 will be described.

[0072] The manufacturing method of insulator 2 mainly includes slurry preparation, degassing, granulation, sieving, forming, grinding and firing processes.

[0073] <Slurry preparation process>

[0074] The slurry preparation process is the process of mixing raw material powder, binder, and solvent to produce a slurry. The raw material powder is a compound powder that is converted into alumina through firing (hereinafter referred to as Al compound powder). For example, alumina powder is used as the Al compound powder.

[0075] The particle size (median diameter) of the Al compound powder is not particularly limited as long as it does not impair the purpose of this invention, but is, for example, 1.5 μm to 2.5 μm. It should be noted that the particle size is the median diameter (D50) on a volume basis, measured using laser diffraction (MIGIC, Microtrac particle size distribution measuring device, product name "MT-3000" manufactured by MIGIC).

[0076] Al compound powder is preferably prepared such that when the mass (oxide conversion) of the sintered alumina-based body is set to 100% by mass, it is 90% or more by oxide conversion. It should be noted that powders other than Al compound powder may be included in the raw material powder, provided that the purpose of the invention is not impaired.

[0077] There are no particular limitations on the amount of adhesive to be mixed, as long as it does not impair the purpose of the present invention. However, for example, it can be mixed in a ratio of 1 to 20 parts by weight relative to 100 parts by weight of raw material powder, preferably in a ratio of 3 to 7 parts by weight.

[0078] There are no particular restrictions on the amount of adhesive to be mixed, as long as it does not impair the purpose of the present invention, but for example, it can be mixed at a ratio of 0.2 to 1.5 parts by weight relative to 100 parts by weight of the raw material powder, preferably at a ratio of 0.3 to 0.9 parts by weight.

[0079] Solvents are used for purposes such as dispersing raw material powders. Examples of solvents include water and alcohol. They can be used alone or in combination of two or more.

[0080] The amount of solvent added is not particularly limited as long as it does not impair the purpose of the present invention, but for example, it is preferably added at a ratio of 35 to 45 parts by weight relative to 100 parts by weight of the raw material powder, and more preferably at a ratio of 38 to 42 parts by weight. It should be noted that, as needed, other components besides the raw material powder, binder, and solvent may also be added to the slurry. In mixing the slurry, known stirring or mixing devices can be used.

[0081] <Defoaming process>

[0082] For slurries prepared after the slurry preparation process, a degassing process can also be performed as needed. In the degassing process, for example, a container holding the mixed (blended) slurry is placed in a vacuum degassing device, and the pressure is reduced to a low-pressure environment, thereby removing air bubbles contained in the slurry. By comparing the density of the slurry before and after degassing, the amount of air bubbles in the slurry can be determined.

[0083] <Granulation Process>

[0084] The granulation process is the process of producing spherical granulated powder from a slurry containing raw material powders, etc. There are no particular limitations on the method of producing granulated powder from a slurry, as long as it does not impair the purpose of this invention; however, spray drying is an example. In spray drying, a slurry is spray-dried using a prescribed spray drying device to obtain granulated powder with a prescribed particle size.

[0085] <Sieving Process>

[0086] The sieving process is a process of removing foreign matter and other contaminants from granulated powder by passing it through a sieve with a specified mesh size. The mesh size of the sieve used in the sieving process is, for example, set to be 150% to 300% of the average particle size of the granulated powder. More specifically, the mesh size of the sieve is adjusted, for example, to a range of 150 μm or more and 350 μm or less.

[0087] <Forming Process>

[0088] The forming process is a process of obtaining a molded body by shaping granulated powder into a specified shape using a forming mold. The forming process is performed by methods such as rubber compression molding and metal mold compression molding. In this embodiment, the pressure (compression rise rate) applied to the forming mold (e.g., the inner and outer rubber molds of a rubber compression molding machine) from the outer periphery is adjusted in a step-by-step manner. It should be noted that during compression molding, by setting a pressure increase stop time of 0.2 seconds or more at a pressure less than half of the maximum compression pressure, residual flattening of the particles disappears, and the size and shape of the pores can be controlled. If a pressure increase stop time is set at a pressure greater than half of the maximum compression pressure, excessive pressure will be applied to the molded body, resulting in defects such as cracks. It should be noted that "pressure increase stop" refers to a situation where the increase or decrease in compression pressure is less than 1 / 20 of the maximum compression pressure.

[0089] <Grinding Process>

[0090] The grinding process involves removing machining allowances from the molded body obtained after the molding process and polishing the surface of the molded body. In the grinding process, machining allowances are removed and the surface of the molded body is polished by grinding with a resin-bonded grinding stone. Through this grinding process, the shape of the molded body is refined.

[0091] <Firing Process>

[0092] The firing process is a process of firing a shaped body that has been shaped by the grinding process to obtain an insulator. In the firing process, for example, it is fired at 1450°C or higher and 1650°C or lower for 1 to 8 hours in an atmospheric atmosphere. By cooling the shaped body after firing, an insulator 2 composed of an alumina-based sintered body is obtained.

[0093] The spark plug 1 of this embodiment is manufactured using the insulator 2 obtained as described above. As mentioned above, the structure of the spark plug 1, except for the insulator 2, is the same as that of known structures.

[0094] The present invention will now be described in further detail based on embodiments. It should be noted that the present invention is not limited to these embodiments in any way.

[0095] [Example 1]

[0096] (Preparation of test samples)

[0097] An insulator (41 in total) with the same basic structure as the spark plug insulator illustrated in Embodiment 1 was manufactured using the same manufacturing method as described in Embodiment 1. The main body of the test sample was cylindrical and had a thickness of 2.0 mm.

[0098] (Determination of withstand voltage in water)

[0099] The following underwater withstand voltage test was conducted, and the through voltage was measured. Details are as follows. Figure 5 This is a schematic diagram illustrating the method of determining the conduction voltage of test sample T1 using an underwater withstand voltage test. (See diagram for example.) Figure 5 As shown, firstly, as preparation for testing relative to the test sample T1 (spark plug insulator 2), a first silicone tube T30 is fitted to the front end 22a of the insulator 2. In this state, silicone rubber T31 is injected into the through hole 21 in the front end 22a for insulation purposes and then cured. It should be noted that the center electrode 3 is pre-adjusted in length by cutting or the like so as not to contact the cured silicone rubber T31. Next, a second silicone tube T32 with an inner diameter larger than the first silicone tube T30 is prepared, and the second silicone tube T32 is fitted to the flange 24 of the insulator 2 such that the front end 22a of the first silicone tube T30 is fitted inside the second silicone tube T32. Then, the gap T33 formed between the second silicone tube T32 and the first silicone tube T30 is soaked in brine (concentration: 1% by mass) T34. In addition, as Figure 5As shown, the center electrode 3 and terminal fitting 5 are inserted into the through hole 21 from the rear end of the rear cylindrical section 25. Then, a test needle T35 is installed on the second silicone tube T32, positioned approximately at the center of the main body 23 along the axial direction of the test sample T1 (insulator 2) and with its front end in contact with the salt water T34. With the test needle T35 thus installed as the grounding side, a high voltage is applied to the terminal fitting 5 exposed from the rear end of the test sample T1 (insulator 2) under the conditions described later. Specifically, while observing the oscilloscope, the voltage is increased at a rate of 1 kV / sec from the starting voltage (20 kV) to 30 kV. The voltage is increased by 1 kV each time from the starting voltage, held at each voltage for 10 seconds, and the voltage sustained is recorded. It should be noted that during the withstand voltage test in water, the wiring on the high-voltage side is placed in the air as much as possible, and only the necessary minimum portion is placed on the insulation. Furthermore, the same center electrode 3 and terminal fitting 5 are used for all test samples T1. This operation was performed on 20 test samples (insulators). The test results were set as the average of the 20 test samples. The results are shown in Table 1.

[0100] (Evaluation of impact resistance)

[0101] Charpy tests, as specified in JIS B7733, were performed on each test sample to determine the fracture energy of the test sample (insulator). The specific details are as follows: First, a spark plug (hereinafter referred to as the test spark plug) with the same structure as the one illustrated in Embodiment 1 above was manufactured using the insulator used as the test sample. The axial direction of the test spark plug was aligned vertically, with the front end facing downwards, and the threaded portion of the main body fitting of the test spark plug was screwed into a threaded hole provided on the test bench for fixation. Furthermore, a hammer with a shaft support point was rotatably mounted above the fixed test spark plug in the axial direction. Then, the front end of the hammer was lifted and released, allowing the hammer to rotate through free fall, causing the front end of the hammer to collide with a portion of the insulator approximately 1 mm from the rear end. The hammer's lifting angle (angle relative to the axial direction) was increased by a predetermined angle each time, while the front end of the hammer collided with the insulator of the test spark plug. This operation was repeated, and the Charpy fracture energy of the insulator was determined based on the lift angle at which the insulator fractured [J]. This operation was performed on 20 test samples (insulators). The test results are set as the average of the 20 test samples. The results are shown in Table 1.

[0102] (Observation of the cross-section of the main stem)

[0103] The main stem of the obtained test sample was cut perpendicularly to the axial direction. The cut surface was then polished to a mirror finish, and the tissue of the cut surface (mirror-polished surface) was observed using SEM. The SEM acceleration voltage was set to 20 kV, and the SEM magnification was set to 500x. Then, 20 observation areas (185 μm × 250 μm) were set in the cut surface (mirror-polished surface) in a non-overlapping manner, and a total of 20 SEM images corresponding to these 20 observation areas were obtained. Then, image analysis processing based on image analysis software (WinROOF (registered trademark)) was performed on these SEM images. For the multiple pores contained in the 20 observation areas, the perimeter length P [μm] and square value P of the pores were calculated. 2 [μm]. Then, the square value P is selected from multiple pores. 2 The upper 20 pores with a diameter of [μm] were selected, and the square value P of the selected 20 pores was calculated. 2 The average value of [μm]. The results are shown in Table 1.

[0104] In addition, the percentage T[%] of the total area of ​​all stomata relative to the total area (100%) of the 20 observation areas was calculated. The results are shown in Table 1.

[0105] Furthermore, for each of the 20 observation regions, the area distribution of stomata was approximated by a log-normal distribution, and the cumulative 50% area [μm] of the cumulative distribution of the stomata area was calculated. The results are shown in Table 1.

[0106] [Examples 2-9]

[0107] Except for appropriately changing the pressing pressure during the pressing stop time in the forming process, test samples of Examples 2 to 9 were made in the same manner as in Example 1.

[0108] [Example 10]

[0109] Except for changing the thickness of the main body to 3.0 mm and changing the pressing pressure during the pressing stop time in the forming process, the test sample of Example 10 was made in the same way as Example 1.

[0110] [Comparative Examples 1 and 2]

[0111] Except that no pressure-increasing stop time was set during the forming pressing process in the forming process, test samples of Comparative Examples 1 and 2 were prepared in the same manner as in Example 1.

[0112] [Comparative Example 3]

[0113] Except for changing the thickness of the main body to 3.0 mm and not setting a stop time for pressurization during the forming process, the test sample of Comparative Example 3 was made in the same manner as in Example 1.

[0114] Regarding the obtained test samples, the above-mentioned "determination of withstand voltage in water", "evaluation of impact resistance", and "observation of the cut surface" were performed, similar to those in Example 1. The results are shown in Table 1. It should be noted that no impact resistance evaluation was performed for Example 10 and Comparative Example 3.

[0115] [Table 1]

[0116]

[0117] As shown in Table 1, in Examples 1-9 where the thickness of the main stem is 2 mm, the square value P... 2 [μm 2 The largest 20 pores are located in the upper part of the pores, and the square value P of these pores is given. 2 [μm 2 The average value is 2200μm. 2 The following describes the excellent voltage withstand performance. It should be noted that in Examples 1-9, the ratio T[%] of the total area of ​​all pores in the 20 observation areas to the total area (100%) of the 20 observation areas was all less than 5.0%. Furthermore, in Examples 1-9, no pores with an area exceeding 5,000 μm were observed.

[0118] In contrast, it was confirmed that in Comparative Examples 1 and 2, where the thickness of the main body was 2 mm, the square value P... 2 [μm 2 The average values ​​were 7820 μm. 2 3420μm 2 Compared with Examples 1-9, the voltage withstand performance is low.

[0119] Furthermore, it was confirmed that Example 10, with a main body thickness of 3 mm, exhibited superior voltage withstand performance compared to Comparative Example 3, which also had a main body thickness of 3 mm.

[0120] Furthermore, it was confirmed that in Examples 1-4 and Examples 8 and 9, the cumulative 50% of the pore area in the cumulative distribution of pore area exceeded 3 μm. 2 In this case, each embodiment has a cumulative area of ​​3 μm. 2 Compared to Examples 5-7 below, it exhibits superior impact resistance.

[0121] In addition, it was confirmed that in Examples 1 and 2 and Examples 5 to 9, the proportion T [%) was all below 3%, and the voltage withstand performance was excellent compared with Examples 3 and 4.

[0122] If the thickness of the main stem is 2mm and the square value P 2 [μm 2 The average value is 1470 μm. 2 Example 1 and the square value P 2 [μm 2 The average value is 7820 μm. 2 Comparing with Comparative Example 1, the difference in withstand voltage in water is 8 kV / mm. In contrast, if the thickness of the main structure is 3 mm and the square value P... 2 [μm 2 The average value is 1465 μm. 2 Example 10 and the square value P 2 [μm 2 The average value is 7820 μm. 2 Comparing with Comparative Example 3, the difference in withstand voltage in water is 5 kV / mm. This confirms that even the squared value P... 2 [μm 2 To the same extent, the smaller the thickness of the main body, the greater the improvement in voltage resistance.

[0123] Explanation of reference numerals in the attached figures

[0124] 1…Spark plug, 2…Insulator, 21…Through hole, 22…Long leg, 23…Main body, 23b…Cut surface (mirror-polished surface), 24…Flange, 25…Rear side cylinder, 26…First diameter expansion, 27…Second diameter expansion, 3…Center electrode, 4…Ground electrode, 5…Terminal fitting, 6…Main body fitting, 7…Resistor, 8…Sealing component, 9…Sealing component, 11…Air hole, AX…Axis.

Claims

1. A spark plug comprising an insulator, said insulator having: a long leg, cylindrical in shape extending along an axial direction and disposed at a front end; a main body, disposed at a rear end of said long leg and having a larger diameter than said long leg; and a flange, disposed at a rear end of said main body and having a larger diameter than said main body, said insulator being composed of an alumina-based sintered body, wherein... In the mirror-polished surface obtained by mirror polishing the cut surface, 20 observation areas of 185μm×250μm were set in a non-overlapping manner, and the square value of the outer perimeter length P[μm] of the pores contained in the 20 observation areas was calculated for each pore. 2 [μm 2 In the case of […], the square value P 2 [μm 2 The square value P of the largest 20 upper pores 2 [μm 2 The average value is 2200 μm. 2 Hereinafter, the cutting surface is obtained by cutting the main stem at any position along the axial direction in a direction perpendicular to the axial direction, and... The ratio T[%] of the total area of ​​all pores in the 20 observation areas to the total area (100%) of the 20 observation areas is less than 5%.

2. The spark plug according to claim 1, The cumulative 50% of the area of ​​the pores in the cumulative distribution of the 20 observation areas is greater than 3 μm. 2 The value of .

3. The spark plug according to claim 1 or 2, The ratio T is below 3%.

4. The spark plug according to any one of claims 1 to 3, The thickness of the main stem is less than 2.0 mm.

Citation Information

Patent Citations

  • Spark plug

    JP2020057559A

  • Spark plug for internal combustion engine, and its manufacturing method

    JP2007250379A

  • Spark plug

    JP2015069828A